Peran Perempuan dalam Mewujudkan Peran Perempuan dalam Mewujudkan Moderasi Beragama Moderasi Beragama - Putri Cahyani, Syabila Gita; Ismail, Shalahudin; Rohman, Ujang (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2023)
Indonesia is unique with a diversity of languages, religions, cultures, tribes, customs and races. This variety of diversity requires religious moderation. Religious moderation is interpreted as a form of tolerance, both towards one's own religion and the religion professed by others. Religious moderation creates religious balance and harmony. This context of tolerance can be formulated as an attitude of openness in different views, by way of expressing and accepting views towards each other's beliefs. In realizing moderation, we need an active role from all parties, including women. Women have great potential in realizing and maintaining the tolerance required in this diverse Indonesia. The purpose of this study is to examine how the role of women in realizing religious moderation. The method used in this study is a descriptive qualitative method that refers to literature data. The results of this study show that the role of women will be the basic capital in realizing moderation in themselves, family, and society. It is hoped that the results of this study can encourage women to be actively involved in carrying out religious moderation.